Pengaruh Brand Ambassador Selebriti Korea Selatan terhadap Niat Beli Produk Perawatan Kulit dan Kosmetik yang Dimoderasi Etnosentrisme Konsumen - Sanaji Sanaji; Mafryanda Safinaturrizqy Addiena Shafa (Jurnal Ilmu Manajemen, 2023)
The phenomenon of many local skincare and cosmetics companies using South Korean celebrity brand ambassadors has been criticized by netizens because South Korean celebrities are considered not to represent Indonesian skin and can create the perception that "only white is beautiful". Based on this phenomenon, the author's purpose in conducting this study is to determine the purchase intention preferences of consumers in Indonesia for South Korean celebrity brand ambassadors on local skincare and cosmetics brands with consumer ethnocentrism as a moderating variable. This study uses quantitative research. Respondents in this study are the users of Somethinc brand, a local skincare and cosmetic product brand, who use Twitter actively and are aged 13 to 38 years. The data obtained from 224 respondents were processed using the PLS-SEM analysis technique with SMARTPLS 4. The results showed that South Korean brand ambassadors affected purchase intention, but consumer ethnocentrism did not moderate the relationship between brand ambassadors and purchase intention. Therefore, this research implies that local skincare and cosmetics brands are expected to use South Korean brand ambassadors to increase consumer purchase intention.